An effective resource management approach in a FaaS environment - Christoforou, Andreas; Andreou, Andreas S. (My University, 2018)
Serverless computing introduces a new Cloud service which consist an increasingly popular architecture for building distributed applications. This paper investigates and proposes a new resource management approach in a FaaS platform, based on intelligent techniques. A number of experiments applied through an indicative framework consisting of a client application and a Lambda function. Three Genetic Algorithms were employed to deliver optimal solutions in a multi-objective environment.
Keywords: Genetic algorithms; Natural resources management; Cloud services; Distributed applications